A HUBUNGAN TINGKAT PENGETAHUAN LANSIA DENGAN NYERI RHEUMATOID ATRITIS DI PUSKESMAS AITINYO BARAT KABUPATEN MAYBRAT - Maylar Gurning; Merlis Simong; Bertha A Bosawer (PT.Mantaya Idea Batara, 2022)
The Maybrat District Health Office based on the records of the Maybrat District health office during 2019 Rheumatoid Arthritis disease was included in the top 10 most cases in Maybrat District, and Rheumatoid Arthritis was in 4th place. suffering from Rheumatoid Arthritis. The purpose of the study was to determine the relationship between the level of knowledge of the elderly with Rheumatoid Arthritis pain in the Work Area of ??the Aitinyo Barat Health Center, Maybrat Regency. This type of research is quantitative research. The research design used was cross sectional. This research was conducted at Aitinyo Barat Health Center, Maybrat Regency. The time of the study was carried out on November 20 - December 02, 2020. The sample of the study was the elderly who came to visit the Aitinyo Barat Health Center, Maybrat Regency with complaints of joint pain (Rheumatoid Arthritis) as many as 42 elderly people. The results of the research that has been carried out with the Chi Square test obtained p = 0.000 <0.05, which means that there is a relationship between the level of knowledge of the elderly and Rheumatoid Arthritis pain in the Work Area of ??the West Aitinyo Public Health Center, Maybrat Regency. The conclusion of this study is that there is a relationship between the level of knowledge of the elderly with rheumatoid arthritis pain at the Aitinyo Barat Health Center, Maybrat Regency. Therefore, it is hoped that the puskesmas officers will provide counseling in the working area of ??the West Aitinyo Public Health Center, Maybrat Regency about Rheumatoid Arthritis disease so that they can increase public knowledge and provide information to the community in handling and how to deal with pain in rheumatoid arthritis sufferers.